Accelerating Waqf Land Certification Problem and Solution through the Complete Systematic Land Registration Program (PTSL) - Acep Zoni Saeful Mubarok; Yuyus Saputra; Darwis Darmawan (Hikmatuna : Journal for Integrative Islamic Studies, 2023)
This paper examines the issues with a comprehensive systematic land registration (PTSL) program's goal of expediting the certification of waqf land. This article focuses on the maintenance of waqf through the waqf certification program. Waqf assets can be preserved by registering waqf land and providing proof in the form of a waqf certificate. Due to their legal standing and ability to settle disputes, the nazhir (managers) and the waqifs (those who contribute land) will feel secure. A government invention to expedite the certification of freehold land, including waqf land, is the PTSL. The program is still in its infancy, thus there are still several issues that pose difficulties and barriers. collaboration and synchronization with other parties. This study uses qualitative techniques and primary data sources, including interviews and direct observation. In addition, literature sources on waqf from regulations, articles and other research become secondary sources. The data that has been collected is analyzed using descriptive analysis techniques. The study's findings revealed, among other things, that the PTSL approach is particularly effective in speeding waqf land certification. Second, there is still a lack of coordination between the Ministry of Religion, BWI, and other organizations, as well as the Agrarian Spatial Planning Office/National Land Agency.